Claw Toe: Anatomic Guide for Injection of Botulinum Toxin into Foot Muscles. (26th January 2022) - Takekawa, Toru; Takagi, Satoshi; Kitajima, Tomohide; Sato, Tomoharu; Kinoshita, Kazuo; Abo, Masahiro
ABSTRACT: Background: Poor response to injection of botulinum toxin (BoNT) into the flexor digitorum longus (FDL) muscle has been reported especially in patients with claw foot deformity. We previously advocated BoNT injection into the flexor hallucis longus (FHL) muscle in such patients. Here, we determined the functional and anatomical relationships between FHL and FDL. Methods: Toe flexion pattern was observed during electrical stimulation of FHL and FDL muscles in 31 post-stroke patients with claw-foot deformity treated with BoNT. The FHL and FDL tendon arrangement was also studied in five limbs of three cadavers. Results: Electrical stimulation of the FHL muscle elicited big toe flexion in all 28 cases examined and second toe in 25, but the response was limited to the big toe in 3. FDL muscle stimulation in 29 patients elicited weak big toe flexion in 1 and flexion of four toes (2nd to 5th) in 16 patients. Cadaver studies showed division of the FHL tendon with branches fusing with the FDL tendon in all five limbs examined; none of the tendons was inserted only in the first toe. No branches of the FDL tendon merged with the FHL tendon. Conclusion: Our results showed coupling of FHL and FDL tendons in most subjects. Movements of the second and third toes are controlled by both the FDL and FHL muscles. The findings highlight the need for BoNT injection in both the FDL and FHL muscles for the treatment of claw-toe deformity.